IDRIS SIREGAR ANALISIS PEMIKIRAN MUHAMMAD SYAHRUR DALAM KAJIAN HADIS - IDRIS SIREGAR (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2022)
Alquran and Hadith is the source for Islamic teachings. This statement is in line with the explanation that the Qur'an is the first main source before the hadith of the Prophet SAW. The study of hadith can be carried out comprehensively in Islamic studies. In history, the crown of Islamic-based knowledge has been mastered by the science of Alquran and hadith, this statement was expressed by Yusuf al-Qardhawi, asserting that Alquran and hadith can turn into masdar and Tsaqafah Islamiyah, this can be seen from the many works of scholars Alquran and hadith. As a masdar in Islamic law, Alquran and hadith continues to be developed to find the right understanding and according to the times, so that Alquran and hadith scholars continue to make efforts in understanding. One of the modern intellectuals who tries to see the side of Alqurana and hadith that is contrary to the majority of scholars, namely Muhammad Shahrur, who in his book as-Sunnah ar-Rasuliyah wa as-Sunnah an-Nabawiyah offers some very controversial ideas, and are often sentenced as heretical by scholars. conservative.